2019
DOI: 10.21037/jtd.2019.03.103
|View full text |Cite
|
Sign up to set email alerts
|

A rapid shallow breathing index threshold of 85 best predicts extubation success in chronic obstructive pulmonary disease patients with hypercapnic respiratory failure

Abstract: Background: The rapid shallow breathing index (RSBI) is used clinically to help predict a patient's likelihood of successful liberation from mechanical ventilation (MV). However, the traditional threshold (<105 breaths/min/L) may underperform in patients with chronic obstructive pulmonary disease (COPD).We sought to determine the optimal RSBI threshold for COPD patients to improve the diagnostic accuracy for predicting successful ventilator liberation. Methods: This was a prospective observational multicenter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…Nevertheless, there was no statistical difference between the age group and the occurrence of DVWR (p<0.05). However, a statistical association was observed between the mean age and the occurrence of DVWR ( p =0.02), which corroborates the findings reported by previous investigations ( 25 , 28 - 29 ) . The association can be partially explained by the morphological and functional changes that occur in the respiratory system with aging, in addition to the greater number of comorbidities in this population.…”
Section: Discussionsupporting
confidence: 91%
“…Nevertheless, there was no statistical difference between the age group and the occurrence of DVWR (p<0.05). However, a statistical association was observed between the mean age and the occurrence of DVWR ( p =0.02), which corroborates the findings reported by previous investigations ( 25 , 28 - 29 ) . The association can be partially explained by the morphological and functional changes that occur in the respiratory system with aging, in addition to the greater number of comorbidities in this population.…”
Section: Discussionsupporting
confidence: 91%
“…[ 16 ] Rapid respiratory rate at the time of extubation could also be a culprit of extubation failure, as it is usually ends in respiratory muscles’ fatigue that may eventually lead to respiratory failure and the need to reinstitute mechanical ventilation. [ 17 ] It logically follows that a lower pH may be a sign of respiratory muscle weakness, and suboptimal breathing rate and depth, thereby contributing to the risk of extubation failure. Gobert et al .…”
Section: Discussionmentioning
confidence: 99%
“…The RSBI is among the most commonly used indices in non-homogeneous populations for predicting successful ventilator liberation. [ 38 48 49 50 ] The accuracy of this measurement, however, has been questioned in the setting of sepsis, fever, supine position, restrictive physiology, and patient anxiety. [ 51 ] One study reported that including the RSBI into a weaning protocol after a decision was made to attempt an SBT prolonged weaning and IMV for an additional day without reducing the number of failed extubations or tracheostomy placements.…”
Section: Discussionmentioning
confidence: 99%
“…[ 55 56 ] Moreover, in the COPD population, an RSBI threshold of ≤85 breaths/min/L outperformed the widely used threshold <105 breaths/min/L, yielding a 95.5% probability of extubation success. [ 50 ]…”
Section: Discussionmentioning
confidence: 99%